2009
DOI: 10.1073/pnas.0909872106
|View full text |Cite
|
Sign up to set email alerts
|

A nonprotein thermal hysteresis-producing xylomannan antifreeze in the freeze-tolerant Alaskan beetle Upis ceramboides

Abstract: Thermal hysteresis (TH), a difference between the melting and freezing points of a solution that is indicative of the presence of large-molecular-mass antifreezes (e.g., antifreeze proteins), has been described in animals, plants, bacteria, and fungi. Although all previously described TH-producing biomolecules are proteins, most thermal hysteresis factors (THFs) have not yet been structurally characterized, and none have been characterized from a freeze-tolerant animal. We isolated a highly active THF from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
118
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 37 publications
0
118
1
Order By: Relevance
“…66 The fact that the polysaccharide examined also contained lipid leaves unresolved whether the polysaccharide or the lipid component was responsible for the activity. 66 This study has demonstrated for the first time the existence of a capsular polysaccharide that in its purified form is endowed with ice recrystallization inhibition activity. Its unique structure, in contrast to that isolated from the beetle U. ceramboides, is strongly related to that of AFGPs, both for the presence of a Thr residue and for the Gal-Gal disaccharide motif.…”
Section: Discussionmentioning
confidence: 99%
“…66 The fact that the polysaccharide examined also contained lipid leaves unresolved whether the polysaccharide or the lipid component was responsible for the activity. 66 This study has demonstrated for the first time the existence of a capsular polysaccharide that in its purified form is endowed with ice recrystallization inhibition activity. Its unique structure, in contrast to that isolated from the beetle U. ceramboides, is strongly related to that of AFGPs, both for the presence of a Thr residue and for the Gal-Gal disaccharide motif.…”
Section: Discussionmentioning
confidence: 99%
“…Such lineages had to overcome selection pressures of shorter growing season, exaggerated daily temperature fluctuations, and seasonal drop of temperatures below the physiological thresholds for activity, growth, and development (7). It is now widely accepted that cold adaptation in insects is highly complex and requires adjustments at all levels of biological organization (8)(9)(10)(11)(12)(13)(14)(15)(16). Supercooling and freeze tolerance are two main strategies that help insects to cope with the risk of water freezing in a cryothermic state.…”
mentioning
confidence: 99%
“…During the extreme winter months, the spruce budworm, Choristoneura hebenstreitella, resists freezing at temperatures approaching −30 °C, while the Alaskan beetle Upis ceramboides can survive in a temperature of −60 °C. [423] …”
Section: Freeze-avoidancementioning
confidence: 99%
“…[420][421][422] AFPs adsorb to the surface of ice and prevent water from joining the crystal lattice, thereby preventing freezing of a solution in the presence of ice until a new, lower freezing point is reached. [423,424] AFPs create a difference between the melting point and freezing point; this phenomenon is known as thermal hysteresis, and it allows insects to survive while their body temperature is below the melting point.…”
Section: Freeze-avoidancementioning
confidence: 99%
See 1 more Smart Citation